Comparative Study Between Peristomal Patches in Patients with Definitive Tracheostomy - Lansaat, Liset (Int Arch Otorhinolaryngol, 2018)
Introduction  To prevent or diminish pulmonary problems in laryngectomized patients, continuous use of a heat and moisture exchanger (HME) is recommended. Therefore, automatic speaking valves are also often combined with an HME to enable hands-free speech. In order to keep these devices in place, most commonly, peristomal patches are used. Objective  This prospective clinical 2 × 2 crossover study aims at assessing the added value of a new patch for HME application, the Provox StabiliBase OptiDerm (SBO). The device combines the stable and conical base of the Provox StabiliBase with the skin-friendlier hydrocolloid Provox OptiDerm (OD) patch. Methods  Thirty-two laryngectomized patients were included in this multicenter study. Participants were asked to compare SBO to OD, and to the patch they normally use. The primary outcome measure was patient preference. Results  Overall, 60% of the participants had preference for their normally used patch, 23% preferred the SBO and 17% indicated no preference. When comparing the SBO to the OD, 43% preferred the SBO, 40% the OD and 17% had no preference. Conclusion  Most patients preferred their normally used patch and SBO was favored by a subgroup. Provox StabiliBase OptiDerm seems to be a valuable addition to the existing patches and further increases patients' options for HME application.